Vegetative propagation of Mikania glomerata: Micro-propagation and cuttings - Pereira, Ana Maria Soares [UNESP]; França, S. C.; Câmara, Francisco Luiz Araújo [UNESP] (My University, 1999)
The scope of this work was to compare two systems for vegetative propagation: conventional one (from cut stems) and in vitro micropropagation from axillary buds. Nodal segments (1 cm) of Mikania glomerata were used as explants. The experiments were evaluated in relation to number of shoots; % of rooting; number of roots and total fresh weight. Multiple shoots developed in MS containing 0.5 mg/L BAP. Rooting was induced in the presence of 1.0 mg/L IBA. Stems with five buds and one pair of leaves were the most appropriate for the production of cuttings. The time necessary for developing a protocol for the production of M. glomerata micropropagated plantlets was 6 months, whereas only half time was required to produce plantlets from stem cuttings. The greatest problem met during micropropagation was the culture contamination by endophytic bacteria and fungi.
Keywords: Guaco; Mikania glomerata; Stalks; Tissue culture